Cilostazol attenuates hepatic stellate cell activation and protects mice against carbon tetrachloride‐induced liver fibrosis. Issue 4 (30th June 2013) - Saito, Shunichi; Hata, Koichiro; Iwaisako, Keiko; Yanagida, Atsuko; Takeiri, Masatoshi; Tanaka, Hirokazu; Kageyama, Shoichi; Hirao, Hirofumi; Ikeda, Kazuo; Asagiri, Masataka; Uemoto, Shinji
<x xml:space="preserve">Abstract</x> Aim Liver fibrosis is a common pathway leading to cirrhosis. Cilostazol, a clinically available oral phosphodiesterase‐3 inhibitor, has been shown to have antifibrotic potential in experimental non‐alcoholic fatty liver disease. However, the detailed mechanisms of the antifibrotic effect and its efficacy in a different experimental model remain elusive. Methods Male C57BL/6J mice were assigned to five groups: mice fed a normal diet (groups 1 and 2); 0.1% or 0.3% cilostazol‐containing diet (groups 3 and 4, respectively); and 0.125% clopidogrel‐containing diet (group 5). Two weeks after feeding, groups 2–5 were intraperitoneally administered carbon tetrachloride (CCl4) twice a week for 6 weeks, while group 1 was treated with the vehicle alone. To investigate the effects of cilostazol on hepatic cells, in vitro studies were conducted using primary hepatic stellate cells (HSC), Kupffer cells and hepatocytes with cilostazol supplementation. Results Sirius red staining revealed that groups 3 and 4 exhibited a lesser fibrotic area (2.49 ± 0.43% and 2.31 ± 0.30%, respectively) than group 2 (3.17 ± 0.67%, P < 0.05 and P < 0.001, respectively). In vitro studies showed cilostazol dose‐dependently suppressed HSC activation (assessed by morphological change, cell proliferation, and the expression of HSC activation markers), suggesting the therapeutic effect of cilostazol is mediated by its direct action on HSC. Conclusion Cilostazol could alleviate CCl4‐induced hepatic fibrogenesis in vivo, presumably due, at least partly, to its direct effect to suppress HSC activation. Given its clinical availability and safety, it may be a novel therapeutic intervention for chronic liver diseases.